Some function spaces on spaces of homogeneous type - Kronz, Manfred (Manuscripta Mathematica, 2001)
We introduce Campanato, Morrey, BMO and Sobolev-type spaces for mappings from a space of homogeneous type into a complete metric space which possess properties comparable to their classical analogues. In particular we show integral characterizations, the validity of the John-Nirenberg theorem, Poincaré and Sobolev inequalities, Sobolev's embedding theorem and estimates on the pointwise behavior of Sobolev-type mappings.
UnivIS-Import:2015-03-09:Pub.2001.nat.dma.lma2.somefu